Proximal femur fracture, analysis of epidemiology, complications, and mortality: A cohort with 380 patients - Yaradılmış, Yüksel Uğur; Okkaoğlu, Mustafa Caner; Ateş, Ahmet; Kılıç, Alparslan; Demirkale, İsmail and Altay, Murat (Journal of Surgery and Medicine, 2021)
Background/Aim: Among all orthopedic injuries, hip fractures continue to have high morbidity and mortality. While the epidemiological features of proximal femoral fractures (PFF) have often been defined, there are studies which examine the relationship between the complications of the types of PFF and mortality. The aim of this study was to determine the frequency of PFF types and investigate the relationship between complications of subtypes and mortality. Methods: This study included 380 patients aged >40 years who underwent surgery for a PFF. The fractures were classified according to localization as intertrochanteric femur fracture (ITFF), femoral neck fracture (FNF) and subtrochanteric fracture (STF). Patient demographic data (age, gender, comorbidities) were recorded, and modified Charlson comorbidity scores were calculated. Major surgical complications (infection, dislocation, implant failure) were defined as those requiring additional surgery, and minor surgical complications (cellulitis, wound site problems, pressure sores, deep vein thrombosis) as those not requiring surgery. Mortality rates were examined at 1, 3 and 12 months postoperatively. The fracture subtypes were compared with respect to surgical complications (major and minor), non-surgical complications and mortality rates. Mortality risk factors were determined according to final mortality status. Results: The patients included 235 females and 136 males (F/M=2/1) with a mean age of 78.5 (12.1) years. Three hundred and thirty (86.5%) patients were aged >65 years and 50 (13.5%) were aged <65 years. The fractures were classified as 225 (60%) ITFF, 120 (32%) FNF, and 26 (7%) STF. Surgical complications and complications not related to surgery were seen in 35 (9.2%) and 25 (6%) patients, respectively. Mortality occurred within one month in 17 (4.6%) patients, in three months in 32 (8.6%) and within the first year in 97 (26%). No significant difference was found between fracture types with respect to mortality in 1, 3, and 12 months (P=0.51, P=0.641, P=0.2 respectively). The mortality rates of ITFF and FNF were highly similar (1, 3, 12-month mortality: P=0.943, P=0.939, P=0.946 respectively). In the comparison between the surviving and non-surviving groups, age, Charlson comorbidity index, prolonged stay in intensive care, and non-surgical complications were significantly increased in the non-surviving group (P<0.001, P<0.001, P=0.03, P=0.005 respectively). Conclusion: ITFF is common among PFF. While there was no relationship between fracture types in PFF, complication and mortality, a correlation was found between mortality and age, Charlson comorbidity score, prolonged stay in intensive care, and non-surgical complications.